Intrinsic Risk Factors of Falls in Elderly - Amatullah, Yasmin; Sastradimaja, Sunaryo B.; Dwipa, Lazuardhi (Althea Medical Journal, 2016)
Background: Falls are common geriatric problems. The risk factors of falls are the intrinsic and extrinsic risk factors. Studies on falls are scarcely conducted in Indonesia, especially in Bandung. Therefore, this study was conducted to identify the intrinsic risk factors of falls among elderly.Methods: A descriptive study was carried out from August to October 2013 at the Geriatric Clinic of Dr. Hasan Sadikin General Hospital Bandung. Fifty three participants were selected according to the inclusion and exclusion criteria using consecutive sampling. The determined variables in this study were classification of the risk of falls, demographic profile, history of falls, disease, and medications. After the selection, the participants were tested by Timed up-and-go test (TUGT). Moreover, an interview and analysis of medical records were carried out to discover the risk factors of falls. The collected data were analyzed and presented in the form of percentages shown in tables.Results: From 53 patients, women (35.66%) were considered to have higher risk of fall than men (18.34%). The majority of patients (66%) with the risk of fall were from the age group 60â74 years. The major diseases suffered by patients were hypertension, osteoarthritis and diabetes mellitus. Drugs that were widely used were antihypertensive drugs; analgesic and antipyretic drugs and antidiabetic drugs.Conclusions: There are various intrinsic risk factors of falls in elderly and each of the elderly has more than one intrinsic risk factor of falls. [AMJ.2016;3(3):334â9]Â DOI: 10.15850/amj.v3n3.875Â